Mechanical Properties and Corrosion Behavior of Thermally Treated Ti-6Al-7Nb Dental Alloy - Hulka, Iosif; Florido-Suarez, Nestor R.; Mirza-Rosca, Julia Claudia; Saceleanu, Adriana (MDPI AG, 2022)
Ti and its alloys have the most satisfactory properties for biomedical applications due to their specific strength, high corrosion resistance, and high biocompatibility. Ti-6Al-7Nb has been approved for clinical use, proving to be a viable replacement for the Ti-6Al-4V alloy that has been used for many decades in medical applications. In our study, the Ti-6Al-7Nb alloy underwent heat treatment, was cooled in various cooling media such as mineral oil and water, and was then quenched in the oven. The microstructure was investigated, and the mechanical characterization was carried out by Vickers microhardness test. Young’s modulus measurements and tensile tests were performed in order to study the effect of cooling media on the material. To study the corrosion behavior, in vitro studies were performed on the Ti-6Al-7Nb samples in simulated body conditions by using artificial saliva. It was observed that the martensitic phase changed as a function of cooling media, and a less intensive cooling medium decreases strength properties’ indicators as well as hardness values. The results emphasize that the use of heat treatment improves the passive layer’s resistance in the presence of artificial saliva.
Keywords: heat treatment; dental alloy; Ti-6Al-7Nb; corrosion resistance